Identifiying of problem solving abilities in Mathematics among Junior High School students - Syaiful Syaiful; Kamid Kamid; Muslim Muslim; Nizlel Huda (Journal of Education and Learning (EduLearn), 2020)
Purpose: This study aims to identify the problem solving abilities possessed by junior high school students. The type of research used is quantitative which uses a research design survey. The sample of this study is  98 students taken based on purposive sampling techniques. This study uses descriptive statistics to analyze the data generated. From the results of the analysis that has been done, it was found that there is a problem solving indicator by students in mathematics which is a indicated by the indicators of planning a solution which has a good category of a 56.1% (55 of 98) students, the indicator of problem solving has a good category of a 56.1% (55 out of 98) students, indicators of a problem solving planning had a good category of a 54.1% (53 of 98) students, and an indicator of understanding a problem had a good category of a 60.2% (59 of 98) students.